Ebola 2016
DOI: 10.5772/63502
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Development of Small Molecule Inhibitors of Ebola Viral Infection

Abstract: The recent outbreak of Ebola viral disease (EVD) in West Africa reminded us that an effective anti-viral treatment still does not exist, despite the significant progress that has recently been made in understanding biology and pathology of this lethal disease. Currently, there are no approved vaccine and/or prophylactic medication for the treatment of EVD in the market. However, the serious pandemic potential of EVD mobilized research teams in the academy and the pharmaceutical industry in the effort to find a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…From the outputs of this paper and also published papers in this field, it is most likely to be said that in silico tools will be of great importance in the life sciences. 3,7,28,30,31 In conclusion, kiwellin like proteins can be existed in not only kiwi but also in different fruits. By using in silico tools, it is more easier to define possible allergen proteins.…”
Section: Algpredmentioning
confidence: 87%
“…From the outputs of this paper and also published papers in this field, it is most likely to be said that in silico tools will be of great importance in the life sciences. 3,7,28,30,31 In conclusion, kiwellin like proteins can be existed in not only kiwi but also in different fruits. By using in silico tools, it is more easier to define possible allergen proteins.…”
Section: Algpredmentioning
confidence: 87%
“…Only a recent work provided the evidence that the binding between VP24 and KPNA may be druggable. 157 Three small molecules extracted from Indian medicinal plants, limonin (Fig. 7), has been identified that blocks the VP24-KPNA5 interaction at low micromolar range in vitro (EC 50 ¼ 9 μM).…”
Section: Vp24 Inhibitorsmentioning
confidence: 99%